Co-ordinating Information Technology in Secondary Schools - Selwood, I. D.; Kennewell, S. (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2022)
Due to the nature of Information Technology in UK secondary schools an essential middle management role has developed over the years - the IT Coordinator (ITC). The ITC is required to combine a daunting number of roles and skills including provision of in-service training (INSET) and cross-curricular support for colleagues, technical expertise, curriculum planning, whole school resource management, etc. The role will vary from school to school. However, this paper endeavours to identify many of the duties, responsibilities and skills commonly required by secondary ITCs. The paper then reports on a survey concerning the professional development needs of secondary ITCs reporting on such aspects as - the nature of the difficulties perceived by ITCs in meeting the demands of their roles; the value of sources of professional development and support available to ITCs; some relationships between contexts, roles, concerns and professional development sources; and draws some conclusions regarding the coordination of IT in secondary schools.